2022
DOI: 10.9734/ijpss/2022/v34i2131244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Parental Lines and their F1 Hybrids for Yield and Attributing Traits in Vegetable Pea [Pisum sativum (L.) var. hortense]

Abstract: The present investigation was carried out to obtain information based on per se performances of parents and their combinations for genetic improvement in vegetable pea. Ten promising genotypes were crossed in a diallel manner (excluding reciprocals). Half diallel set of 45 F1’s in vegetable pea was evaluated in Randomized Complete Block Design (RBD) with three replications for eighteen yield and yield attributing traits during Rabi 2020-21 (Y1) and 2021-22 (Y2) at the Main Experimental Station (MES), Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The selection of parents having high per se performance would be of merit in producing better hybrids and hence the parents selected for the crossing program were evaluated based on their per se performances. The most important trait fruit yield per plant and other quality traits results for pooled data are discussed below" [4]. A perusal of Table 1 revealed that days to 50% flowering ranged from 28.71 to 41.47 for parents and F 1 hybrids with an overall mean of 35.50.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of parents having high per se performance would be of merit in producing better hybrids and hence the parents selected for the crossing program were evaluated based on their per se performances. The most important trait fruit yield per plant and other quality traits results for pooled data are discussed below" [4]. A perusal of Table 1 revealed that days to 50% flowering ranged from 28.71 to 41.47 for parents and F 1 hybrids with an overall mean of 35.50.…”
Section: Resultsmentioning
confidence: 99%
“…The present investigation was carried out at the Main Experimental Station, Department of Vegetable Science, Acharya Narendra Deva University of Agriculture and Technology, Narendra Nagar (Kumarganj), Ayodhya (UP), India, during Rabi, 2021-22 (Y 1 ) and 2022-23 (Y 2 ). "The experimental farm falls under a humid subtropical climate and is located between 24.47° and 26.54°N latitude and 81.84° and 83.58°E longitude at an altitude of 98 m above mean sea level" [4].…”
Section: Methodsmentioning
confidence: 99%